Characterization of polymorphic microsatellite markers for Primula sikkimensis (Primulaceae) using a 454 sequencing approach(1) - Li, Chang-Han (Appl Plant Sci, 2016)
PREMISE OF THE STUDY: Microsatellite markers from Primula sikkimensis (Primulaceae) were developed for testing deep lineage divergence and speciation events. METHODS AND RESULTS: A total of 3112 microsatellites were identified from 61,755 unique reads though 454 pyrosequencing technology. Twenty-nine microsatellite loci were selected for PCR amplification and polymorphic analyses. Among the 29 tested markers, 17 microsatellite loci were further used for genotyping in three wild P. sikkimensis populations. The number of alleles varied from one to eight, and the observed heterozygosity ranged from 0.111 to 1.000. Ten simple sequence repeat loci could be successfully cross-amplified in two Primula species. The transferability values were 76.5% in P. florindae and 58.8% in P. alpicola, respectively. CONCLUSIONS: These microsatellite markers will be valuable for testing the hypothesis of lineage divergence, genetic introgression, and cryptic speciation events between P. sikkimensis and its closely related taxa.